Efficacy of a pressure-sensing mattress cover system for reducing interface pressure: study protocol for a randomized controlled trial. Issue 1 (December 2015) - Wong, Holly; Kaufman, Jaime; Baylis, Barry; Conly, John; Hogan, David; Stelfox, Henry; Southern, Danielle; Ghali, William; Ho, Chester
Abstract Background Interface pressure is a key risk factor in the development of pressure ulcers. Visual feedback of continuous interface pressure between the body and support surface could inform clinicians on repositioning strategies and play a key role in an overall strategy for the prevention and management of pressure ulcers. Methods/Design A parallel two-group randomized controlled clinical trial will be conducted to study the effect of continuous pressure imaging on reducing interface pressure and on the incidence of pressure ulcers in vulnerable hospital patients. A total of 678 eligible consenting inpatients at risk of pressure ulcer development in a tertiary acute care institution will be randomly allocated to either having the ForeSite PT™ system with the liquid-crystal display monitor turned on to provide visual feedback to the clinicians while also collecting continuous interface pressure data (intervention group) or to having the ForeSite PT™ system with monitor turned off (that is, not providing visual feedback) but still collecting continuous interface pressure data (control group), in a ratio of 1:1. Continuous interface pressure data will be collected in both groups for 3 days (72 h). Data collection will continue until discharge for a subset of approximately 60 patients. The primary outcome will be the differences in the two groups' interface pressure analysis. Interface pressure readings will be collected through hourly samplings of continuous interface pressure recordings. Secondary outcomes will be the differences between the two groups in pressure-related skin and soft tissue changes in areas at risk of pressure ulcer (obtained at baseline within 24 h of admission) and on the third day of the trial or at discharge and perceptions of the intervention by patients and clinicians (obtained on the third day or at discharge). Discussion This will be the first randomized controlled trial to investigate the effect of visual feedback with continuous interface pressure of vulnerable hospital patients across different care settings, and the association between interface pressure and development of pressure-related skin and soft tissue changes. The results could provide important information to guide clinical practice in the prevention and management of pressure ulcers. Trials registration ClinicalTrials.govNCT02325388 (date of registration: 24 December 2014).